Utilization of the SIMPACA Application to improve the quality of nursing care documentation for nurses - Jum Natosba; Jaji Jaji; Nurna Ningsih; Herliawati Herliawati; Fuji Rahmawati; Karolin Adhisty (University of Merdeka Malang, 2022)
The phenomenon of nurses in hospitals being preoccupied with recording documentation activities manually compared to providing independent nursing care to patients. One of the reasons for improving the behavior of nurses in documenting nursing care is increasing the ability of nurses to do documentation using application assistance to facilitate the work of nurses. This community service activity aims to improve the ability of nurses to document effectively and efficiently. The activity was carried out for two days through a zoom meeting. Previously, at the beginning of the activity, a nurse's ability pre-test was conducted and at the end of the session, another measurement was made for the nurse's ability. Community service activities were carried out with 45 nurses in South Sumatra. During the activity, the participants were very enthusiastic in listening, discussing with resource persons, and doing simulations well. There is an increase in documentation ability before and after the documentation training using SIMPACA is carried out. SIMPACA is proven to be effective in improving nurses' documentation skills and reducing nurses' time in documenting their nursing care to patients. There is a need for further development of SIMPACA because it must adapt to the needs of the hospital.